Simula??o de desempenho de sistemas com m?ltiplas portadoras com ceifamento de pico em Canais AWGN - Geovanini, Carolina Vieira (2005)
Abstract: The OFDM technique has been researched in worldwide institutions because of the many services that require high transmission rates. This technique has been adopted in various standards of digital communication, such as xDSL system used in the last mile, digital television standards ISDB-T Japanese and European DVB-T. Thus, there was a significant increase of interest in the technique with multiple carriers. The first major difficulty is related to the generation and reception of the OFDM signal is used when a large number of subcarriers. To not compromise the orthogonality between subcarriers these, one should ensure that there is synchronism between the complex N oscillators of the transmitter and receiver. With the development of digital signal processors, it was possible to solve this problem, using the method of the IFFT / FFT and thus enabling the implementation of the OFDM technique. Another difficulty relates to the signal amplification due to the occurrence of high amplitude peaks in the OFDM signal, since this signal has a high ratio between its peak power and average power. In order to reduce costs, RF power amplifiers are designed to possess high yield, ie, operating as close to the saturation point. Thus, the OFDM signal of the high amplitude peaks are harvested by introducing a non-linear distortion in the signal. The main objective of this work is to simulate the performance of OFDM systems with peak ceifamento channels with and without AWGN noise. First, we present the methods used for the generation and reception of the OFDM signal, they study their statistical characteristics and the reasons that lead to the occurrence of ceifamento. Then, two methods are presented for modeling ceifamento and develops the probability of symbol error for both models. It should be noted that the modeling ceifamento as impulsive noise is the most adequate to estimate the probability of symbol error due to ceifamento. Also analyzes the AWGN channel and develops the probability of symbol error due to ceifamento the amplitude of the OFDM signal in AWGN channels. Finally compares the theoretical results on the performance of OFDM systems with ceifamento in noisy channels with the results obtained from computer simulation.